IMPACT OF AI IN CUSTOMER SERVICES RETENTION: A BEHAVIORAL PERSPECTIVE OF INDIAN MOBILE MARKET - Kunal, Kishore (Digital Repository of Theses, 2022)
In this research, I have explored customer retention as one of the most significant advancements in membership-based business models. To obtain a competitive advantage, businesses use electronic commerce channels to engage with mobile users. For example, competition is severe in the market, where clients can explore a large selection of vendors, even within the same product category. After a few negative experiences, a customer may discontinue purchasing services or products from a specific company. According to this study, customers' perceptions of their interactions with firm staff may be influenced by negative emotions. Some clients may be dissatisfied, while others may sympathise with the personnel at issue. This reaction is represented in their emotional abilities, which the scientific world refers to as emotional intelligence. As a result, the title of this study paper includes several aspects that influence consumer behaviour and are influenced by Artificial Intelligence (AI). A typical AI system operates by consuming huge volumes of labelled training data, analysing it for correlations and patterns, and then forecasting future states. Because AI programming focuses on obtaining data and generating rules to turn it into meaningful information, its learning processes are overly powerful. Artificial intelligence automates the data review process, providing previously unreachable insights that assist clients in better understanding their needs. Consumer behaviour in the mobile industry, particularly consumer behaviour, has become a prominent marketing research topic. Every consumer has distinct life experiences that influence their shopping decisions. Age, employment, lifestyle, personality, and self-concept are social and personal elements that can affect a buyer's final selection. The Indian mobile market is still in its early stages, and several smartphone manufacturers see it as a potential market. "Some major international companies are Samsung, Apple, Sony, Nokia, Motorola, LG, and so on. However, the market share of international brands is decreasing as local brands such as Micromax and Karbonn launch smartphones with Android operating systems and large screens at much lower prices than international brands." The rapid developments in practically every business type underline the importance of relationships and the need to build networks of ties. Mobile commerce has become indispensable in all parts of life, including education, health, business, and entertainment. Mobile phones are "telephones that are portable and not coupled to a base unit that operates on specialised mobile phone networks and generates income from all speech and data transfers emanating from such mobile phones." Based on tests performed on data collected, several outcomes were discovered. In this research, the participants were chosen using the technique described, and their data were analysed using descriptive and inferential statistics. The Chi-Square test was used to investigate the relationship between the individual domain of AI and the age of the consumer who considers it important, as well as the relationship between companies and their usage of optimal service techniques. According to the study's findings, a customer-journey analytics solution records each customer's moves across its ecosystem in the telecom business. The service creates maps of each journey and records visitor interactions. Comcast quickly resolves customer experience issues using AI to collect data and detect where trips fail, such as with its mobile app. Businesses are integrating different AI, Martech, and back-office technologies with standard application programming interfaces to generate and use customised data more effectively. Users can interact with businesses in innovative ways thanks to new digital media. Users may give these individualised client experiences while alleviating the pressure on your support staff by utilising AI and cognitive search. For instance, the performance of content in your self-service community determines the content ranking agents see in the CRM. Within your customer community, the content that agents utilise to resolve situations is pushed to the top of search results. This closes the loop between self-service and assistance, allowing you to provide seamless experiences for your customers. AI-powered solutions may aid organisations in encouraging customers to take action at each stage of the user life cycle.